A Proposed Genetic Algorithm for Multicast Routing - Muna Mohammed Al-Nayar; Abdul Kareem Mahmod Shukri (Engineering and Technology Journal, 2010)
Many Internet applications (such as video conferences) are one-to-manyor many-to-many, where one or multiple sources are sending to multiple receivers. These applications need certain Quality of Services to be guaranteed in underlying network. This paper presents a genetic multicast routing algorithm which finds the low-cost multicasting tree from a designated source to multiple destinations with Quality of Service (QoS) (i.e., bandwidth and end-to-end delay) constraints.Experimental results show that the proposed algorithm finds the minimum-cost multicast routing tree while satisfying QoS constraints and could finally converge to the global optimal solution for a large-scale network.